IDENTIFICAÇÃO DAS ÁREAS DE VULNERABILIDADE SOCIOAMBIENTAL MEDIANTE LÓGICA FUZZY – ESTUDO NO MUNICÍPIO DE PONTA GROSSA, PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This research identifies the different environmental vulnerability indices from fuzzy logic in urban area of Ponta Grossa, Paraná. Noteworthy is the use of geotechnology, and representation in the making cartograms and maps as well as in intersection and thematic analysis. The research raises the environmental profile of urban space of the city, through the data collected by IBGE Census 2010 and the steepness of the municipality. Employs the methodology for creating fuzzy indices, characterizing the data in (5) analysis groups, housing conditions, conditions as to access to education and economic conditions, subnormal agglomerates and relief conditions with rates ranging from 1 better and 0 the worst conditions of the studied phenomenon. By Fuzzy operators AND, OR, PRODUCT, SUM and GAMMA, intersect the vulnerability groups representing different levels of vulnerability in different fuzzy operators, representing the socioeconomic vulnerability. The environmental vulnerability index is the end result, results from overlapping fuzzy with all the groups that make up the index of socioeconomic vulnerability added to the group index slope by AND and GAMMA. The operators performed well, identifying the different levels of vulnerability and the least vulnerable sectors are present in the district center and in its vicinity, in more distant neighborhoods mostly vulnerabilities are higher.
Keywords: vulnerabilidade socioambiental; Lógica Fuzzy; espaço urbano; environmental vulnerability; Fuzzy Logic; urban space; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA